DNA Barcoding of Moon Jellyfish (Cnidaria, Scyphozoa, Ulmaridae, Aurelia): Two Cryptic Species from the Azores (NE Atlantic, Macaronesia), and Evaluation of the Non-Indigenous Species (NIS) - Carlos J. Moura; Bruno I. Magalhães; João M. Gonçalves (Diversity, 2023)
Moon jellies are some of the most popular, widely distributed, and best-studied marine jellyfish. By the end of the past century only two or three Aurelia species were recognized, but with the rise of DNA barcoding studies, around thirty Aurelia species are presently accepted. Most of the species are morphologically indistinguishable and have restricted biogeography. We reveal, with COI, 16S, and ITS1-5.8S sequence data, two (pseudo-)cryptic species of Aurelia, potentially endemic to the Azores ecoregion, herein provisionally classified as A. “cf. pseudosolida” and A. “misteriosa”. These species are closely related to the Mediterranean lineages of A. pseudosolida and A. persea, respectively. In the Azores, the shape of the campanula and oral arms readily distinguishes the two species: the former with folded oral arms and globose campanula, and the latter with flattened campanula and thick and long oral arms. Previous reports of A. solida and A. aurita in the Azores should generally correspond to A. “misteriosa” and A. cf. pseudosolida, respectively. The phylogenetic (re-)examination of the available DNA barcodes of Aurelia only evidenced human-mediated dispersal for A. coerulea, A. relicta, and A. aurita. Aurelia solida cannot be yet considered NIS in the Mediterranean. More jellyfish DNA (meta)barcoding should reveal further cryptic diversity, biological invasions, and phylogeographic inferences.